Clinical presentation and airway management of tracheal atresia: A systematic review. (October 2017) - Smith, Mariana M.; Huang, Amy; Labbé, Mathilde; Lubov, Joshua; Nguyen, Lily H.P.
Abstract: Objectives: Tracheal atresia (TA) is a rare congenital condition that typically requires an unexpected and emergent resuscitation in the delivery room. The mortality rate associated is very high, with only a few long-term survival cases reported. We describe the findings of a systematic review on the clinical presentation and airway management of TA. Methods: Using the keywords "tracheal atresia", "tracheal agenesis" and "tracheal hypoplasia" a search through Embase and Pubmed databases was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. Articles published from 1950 to 2015 in English, French, Italian, Portuguese and Spanish were included. Exclusion criteria were cases of stillborn, and unclear diagnosis or outcome. Results: 149 cases of TA were identified after reviewing 1125 initial references. There was a male preponderance (65%), and associated malformations were described in 94.2% of patients. Prenatal ultrasound was abnormal in 56.3% of cases, with polyhydramnios being the most common finding. The most frequent type of TA was Faro Type C. 94 (41.3%) patients did not survive beyond the first 24 h of life. Only 13 (8.4%) patients survived more than three months of life, after undergoing a variety of surgical approaches. Conclusion: This review, which to our knowledge is the largest one to date, confirms that TA is a rare malformation, occurs more frequently in males, and has a very high mortality rate. Depending on the presence and type of concomitant malformation, as well of the length of the remaining trachea, different surgical management options are described.